Pharmacological Advances for Treatment in Hypertension - Arquimedes Gasparotto Junior (MDPI AG, 2023)
Hypertension plays a significant role in the development of cardiovascular disease and renal diseases, which can heighten the likelihood of experiencing related conditions like myocardial infarction, stroke, and heart failure [...]